2013
DOI: 10.1177/1363460713497214
|View full text |Cite
|
Sign up to set email alerts
|

Representations of sex workers’ needs and aspirations: A case for arts-based research

Abstract: This article reviews the literature on sex work, highlighting ways in which women working in the sex industry are represented. The subjective experiences and voices of sex workers are seldom heard and their needs are consistently defined and represented by non-sex workers throughout history, in society and within academia. Historical representations have contributed to the stereotyping and stigmatization of sex workers. Academic research is consistently being done on sex workers instead of with them. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Kantola and Squires (2004) frame impacts into nuisance or moral discourses, with environmental nuisance (more associated with on-street sex work) including litter and noise (Benson and Matthews, 2000), fear of going out after dark, or being mistaken for sex workers/clients (Kingston, 2013;O'Neill et al, 2008), and criminality ranging from public urination to sexual crimes . Historical fears of contracting venereal disease from discarded condoms in public spaces, or clients infecting non-sex worker populations (Whittaker and Hart, 1996) still pervade certain stereotypes about sex work now (Desyllas, 2013). Moral discourses (more associated with off-street sex work) surround the corruption of the community (especially children) by witnessing soliciting, or the decay of 'family-orientated' neighbourhoods (Prior and Crofts, 2012).…”
Section: The Community Sex Factor: Problems With Impact Discoursesmentioning
confidence: 99%
“…Kantola and Squires (2004) frame impacts into nuisance or moral discourses, with environmental nuisance (more associated with on-street sex work) including litter and noise (Benson and Matthews, 2000), fear of going out after dark, or being mistaken for sex workers/clients (Kingston, 2013;O'Neill et al, 2008), and criminality ranging from public urination to sexual crimes . Historical fears of contracting venereal disease from discarded condoms in public spaces, or clients infecting non-sex worker populations (Whittaker and Hart, 1996) still pervade certain stereotypes about sex work now (Desyllas, 2013). Moral discourses (more associated with off-street sex work) surround the corruption of the community (especially children) by witnessing soliciting, or the decay of 'family-orientated' neighbourhoods (Prior and Crofts, 2012).…”
Section: The Community Sex Factor: Problems With Impact Discoursesmentioning
confidence: 99%
“…The dominatrices' self-representations echo neoliberal policy objectives stressing the individual's responsibility for one's own personal development. Similar empowered approaches have been identified among other groups of prostitutes (Augustin, 2008;Day, 2009;Desyllas, 2013;Tomkinson, 2012), who often see themselves as entrepreneurs in business (Bernstein, 2007). What is more, parts of the sociological literature suggest that entering into prostitution is a personal decision-indeed, a perfectly rational choice based on negotiating the pros and cons, despite the constraints of structural factors such as poverty, crime, education, and employment opportunities (Bernstein, 2007).…”
Section: Tailoring Of Exit Programsmentioning
confidence: 55%
“…It is essential to enable social workers and volunteers to improve their approach to the different types of prostitute, as the former in many countries are the first to contact the prostitutes and therefore play a central role in implementing exit programs. As public debates are dominated by opposing positions drawing selectively on the evidence of the possible long-term effects of prostitution and trafficking (Bjønness, 2012;Bjørnholk, 1994;Bodström & von Zweigbergk, 1994;Desyllas, 2013;Høigård & Finstad, 1987), the various research conclusions available should be communicated to social workers and volunteers so that they become aware of the nuances in both the sex worker organizations' arguments and the prohibitionists' arguments. They should be aware of conclusions like Pheterson's (1996), who found that prostitutes may suppress their own feelings when they provide sexual services to avoid suffering long-term emotional consequences or subsequent deleterious effects of a social, psychological, or sexual kind, as well as of studies of self-defence (for instance, Armstrong, 2011;Comack & Seshia, 2010;Shannon et al, 2008).…”
Section: Tailoring Of Exit Programsmentioning
confidence: 99%
“…Sex workers often represent one of the more marginalized and stigmatized groups in Canada. In this article, the term "sex work" refers to adults over 18 years of age who engage in a range of activities where sexual services are exchanged for money or other goods (Capous Desyllas, 2013). Accessing supports present numerous challenges for sex workers, as the ideological stance of organizations often inform the types of direct services and programming available.…”
Section: Sex Work and Direct Services: Underlying Ideologiesmentioning
confidence: 99%
“…While organizations that provide direct services for sex workers use social media, our knowledge of the online presence and strategies of how social media channels are used is limited. There is also a recent call amongst scholars in the field of sex work for the need to understand the role of social media amongst organizations that provide direct services to sex workers (Beer, 2011;Capous Desyllas, 2013;Oselin & Weitzer, 2013). As noted by Beer, "we have yet to measure the process and impact of online consciousness-raising, and coalition building, but technology has certainly impacted and perhaps expanded the movement, putting people in contact with one another in ways that were not possible before" (2011, p. 91).…”
Section: Direct Services and Social Media: Digital Literacy And Knowlmentioning
confidence: 99%